Evaluation of dry eye parameters among electronic cigarette smokers - Ping, Chew Rui (2023)
Introduction The emergence of electronic cigarettes as the “healthier” version of smoking has been popular these days, especially among young adults. However, the knowledge about the potential effects of e-cigarettes on ocular structures is scarce. This study investigates on the effects of electronic cigarette smoking on dry eye parameters. Objective To compare the mean change in dry eye parameters between electronic cigarette smokers and non-smokers, and to correlate between dry eye parameters with device power output. Methodology This is a cross-sectional, single-visit study conducted between January 2021 to June 2022 in ophthalmology clinics of Hospital Tengku Ampuan Afzan (HTAA) and Hospital Universiti Sains Malaysia (HUSM). 85 electronic cigarettes smokers who aged between 18 to 45 years, attending quit smoking clinics of HTAA and HUSM, or electronic cigarette retail shops around Kuantan, Pahang and Kubang Kerian, Kelantan, and fulfilled the inclusion and exclusion criteria were recruited. Another group of 85 non-smokers were recruited as control. Electronic cigarettes smokers were being interviewed on electronic cigarette smoking duration, number of puffs taken per day and device power output used. Subsequently, all participants were evaluated on dry eye parameters, including Ocular Surface Disease Index (OSDI) questionnaire, tear meniscus height (TMH), tear break-up time (TBUT), cornea fluorescein staining and Schirmer’s I test. Mean change in dry eye parameters was compared between electronic cigarette smokers and non-smokers. Correlation between dry eye parameters with device power output was analysed. Results All participants recruited are males. The mean age of electronic cigarette smokers was 29.3+8.1 years, whereas the mean age for the non-smokers was 28.64+6.7 years. For dry eye symptoms (OSDI score), median (IQR) of 0.00(0.00-6.25) among the electronic cigarette smokers and 0.00(0.00-2.08) among the non-smokers were obtained (p=0.101). 32.94% of e-cigarette smokers were found to have a TMH<0.2mm, compared to only 5.88% of non-smokers with TMH<0.2mm (p<0.001). Significant change in mean TBUT was found between the e-cigarette smokers, 10.41+2.65 sec, and non-smokers, 12.66+3.14 sec (p-value<0.001). No significant change in the median corneal fluorescein staining score (p=0.061). Lower mean Schirmer’s I test was found among electronic cigarette smokers, 12.75+7.24mm, compared to non-smokers, 20.02+7.98mm (p<0.001). OSDI score and device power output were found to have significant positive correlation (r=0.315, p=0.003). There was significant association between dry eye signs and device power output, in which reduced TMH (r=-0.216, p=0.047), TBUT (r=-0.330, p=0.002), and Schirmer’s I test readings (r=-0.488, p<0.001), as well as increased corneal fluorescein staining (r=0.378, p<0.001) were reported with the increase in device power output. Conclusions There is significant mean change in TMH, TBUT and Schirmer’s I test reading among electronic cigarette smokers compared to non-smokers. Higher electronic cigarette device power output results in more dry eye symptom with higher OSDI score. Higher electronic cigarette device output also results in more dry eye signs, including reduced TMH, TBUT and Schirmer’s I test readings, as well as increased corneal fluorescein staining. Therefore, concern should be raised on the risk of electronic cigarette use on ocular health and regulation on e-cigarettes ban should be revisited.